Landscape of copy number aberrations in esophageal squamous cell carcinoma from a high endemic region of South Africa - Jacqueline Brown; Andrzej J. Stepien; Pascale Willem (BMC Cancer, 2020)
Abstract Background Esophageal squamous cell carcinoma (ESCC) is an aggressive cancer with one of the highest world incidences in the Eastern Cape region of South Africa. Several genome wide studies have been performed on ESCC cohorts from Asian countries, North America, Malawi and other parts of the world but none have been conducted on ESCC tumors from South Africa to date, where the molecular pathology and etiology of this disease remains unclear. We report here tumor associated copy number changes observed in 51 ESCC patients’ samples from the Eastern Cape province of South Africa. Methods We extracted tumor DNA from 51 archived ESCC specimens and interrogated tumor associated DNA copy number changes using Affymetrix® 500 K SNP array technology. The Genomic Identification of Significant Targets in Cancer (GISTIC 2.0) algorithm was applied to identify significant focal regions of gains and losses. Gains of the top recurrent cancer genes were validated by fluorescence in situ hybridization and their protein expression assessed by immunohistochemistry. Results Twenty-three significant focal gains were identified across samples. Gains involving the CCND1, MYC, EGFR and JAG1 loci recapitulated those described in studies on Asian and Malawian cohorts. The two most significant gains involved the chromosomal sub-bands 3q28, encompassing the TPRG1 gene and 11q13.3 including the CTTN, PPFIA1and SHANK2 genes. There was no significant homozygous loss and the most recurrent hemizygous deletion involved the B3GAT1 gene on chromosome 11q25. Focal gains on 11q13.3 in 37% of cases (19/51), consistently involved CTTN and SHANK2 genes. Twelve of these cases (23,5%), had a broader region of gain that also included the CCND1, FGF19, FGF4 and FGF3 genes. SHANK2 and CTTN are co-amplified in several cancers, these proteins interact functionally together and are involved in cell motility. Immunohistochemistry confirmed both Shank2 (79%) and cortactin (69%) protein overexpression in samples with gains of these genes. In contrast, cyclin D1 (65%) was moderately expressed in samples with CCND1 DNA gain. Conclusions This study reports copy number changes in a South African ESCC cohort and highlights similarities and differences with cohorts from Asia and Malawi. Our results strongly suggest a role for CTTN and SHANK2 in the pathogenesis of ESCC in South Africa.